2012
DOI: 10.1107/s1744309112015333
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic analysis of human peptidylarginine deiminase type III

Abstract: In the presence of calcium ions, human peptidylarginine deiminase (PAD) converts arginine residues in proteins to citrulline. Of the five known human PAD enzymes, the type III isozyme (PAD3) exhibits the highest specificity for synthetic and natural substrates. This study aimed to determine the structure of PAD3 in order to elucidate its selective citrullination mechanism. Crystals of PAD3 obtained using polyethylene glycol 400 as a precipitant diffracted to 2.95 Å resolution using synchrotron radiation. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…PAD2, PAD3 and PAD4 are homodimers, whereas PAD1 is a monomer in solution. Crystallization and preliminary Xray crystallographic analysis of human PAD3 have been studied, and the structures of PAD family have been uncovered more comprehensively [70].…”
Section: Pad Familymentioning
confidence: 99%
“…PAD2, PAD3 and PAD4 are homodimers, whereas PAD1 is a monomer in solution. Crystallization and preliminary Xray crystallographic analysis of human PAD3 have been studied, and the structures of PAD family have been uncovered more comprehensively [70].…”
Section: Pad Familymentioning
confidence: 99%
“…Unfortunately, the little structural information presently available on the three PAD isoforms (PAD1, PAD2, and PAD3) in the hair follicle neither account for their different substrate specifi cities nor allow elucidation of the consensus recognition site of the target proteins. Further study is necessary to reveal the structural accommodation between S100A3 and recently crystallized PAD3 (Unno et al 2012 ).…”
Section: Structural Insights Into Pad Target Recognitionmentioning
confidence: 99%
“…Subsequently, PAD2 exhibits broad catalytic activity for S100A3, resulting in extensive conversion of other sites (Kizawa et al 2008 ). Because PAD3 is predicted to form a dimer (Unno et al 2012 ), its catalytic reaction proceeds in a heterotetrameric substrate-enzyme complex (left side of Fig. 8.6 ).…”
Section: Znmentioning
confidence: 99%
“…The Histagged PAD1 protein was expressed in Escherichia coli BL21(DE3)pLysS cells and purified using a His-tag affinity column, as reported previously for PAD3 (Unno et al, 2012). Briefly, cells cultured in 500 ml Luria Bertani medium were disrupted by sonication at 277 K in buffer A [20 mM Tris-HCl buffer pH 7.6, 400 mM NaCl, 10%(v/v) glycerol, 10 mM -mercaptoethonol] supplemented with 1 mM phenylmethanesulfonyl fluoride.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…X-ray crystallographic analyses of human PAD4 (Arita et al, 2004(Arita et al, , 2006 and PAD3 (Unno et al, 2012) showed that these isozymes form a dimer with a similar overall structure; however, no structural information is currently available for the other isozymes. To elucidate the catalytic mechanism that confers broad substrate specificity, it is necessary to determine the X-ray structures of PAD1 and PAD2.…”
Section: Introductionmentioning
confidence: 99%